Pain, mood, and suicidal behavior among injured working adults in Chile - Juan Carlos Vélez; Michael Kovasala; Michele Demi Collado; Lauren E. Friedman; Diana L. Juvinao-Quintero; Lisette Araya; Jessica Castillo; Michelle A. Williams; Bizu Gelaye (BMC Psychiatry, 2022)
Abstract Background Chronic pain is comorbid with psychiatric disorders, but information on the association of chronic pain with depressive symptoms, generalized anxiety, and suicidal behavior among occupational cohorts is inadequate. We investigated these associations among employed Chilean adults. Methods A total of 1946 working adults were interviewed during their outpatient visit. Pain was assessed using the Short Form McGill Pain questionnaire (SF-MPG) while depression and generalized anxiety were examined using the Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7), respectively. The Columbia–Suicide Severity Rating Scale was used to assess suicidal behavior and suicidal ideation. Multivariable logistic regression models were used to estimate adjusted odds ratios (aORs) and 95% confidence intervals (95%CI) for the association of chronic pain with mood disorders, as well as suicidal behavior. Results High chronic pain (SF-MPG > 11) was reported by 46% of participants. Approximately two-fifths of the study participants (38.2%) had depression, 23.8% generalized anxiety, 13.4% suicidal ideation, and 2.4% suicidal behavior. Compared to those with low pain (SF-MPG ≤11), participants with high chronic pain (SF-MPG > 11) had increased odds of experiencing depression only (aOR = 2.87; 95% CI: 2.21–3.73), generalized anxiety only (aOR = 2.38; 95% CI: 1.42–3.99), and comorbid depression and generalized anxiety (aOR = 6.91; 95% CI: 5.20–9.19). The corresponding aOR (95%CI) for suicidal ideation and suicidal behavior were (aOR = 2.20; 95% CI: 1.58–3.07) and (aOR = 2.18 = 95% CI: 0.99–4.79), respectively. Conclusions Chronic pain is associated with increased odds of depression, generalized anxiety, and suicidal behavior. Mental health support and appropriate management of patients experiencing chronic pain are critical.